LO53: Resuscitation status documentation availability among emergency patients with advanced disease. (15th May 2017) - Russell, E.; Hall, A.K.; McKaigney, C.; Goldie, C.; Harle, I.; Sivilotti, M.
Abstract : Introduction: Patients with advanced malignant and non-malignant disease (advanced disease—AD) who do not want or benefit from aggressive resuscitation may unfortunately receive such treatments if unable to communicate in an emergency. Timely access to patients' resuscitation wishes is imperative for treating physicians and for medical information systems. Our aim was to determine what proportion of emergency department (ED) patients with AD have accurate, readily accessible resuscitation status documentation.Methods: This cross-sectional, prospective study was conducted at a tertiary care ED during purposefully sampled random accrual times in summer 2016. We enrolled all patients with: 1) palliative care consultation, 2) metastatic malignancy, 3) COPD or CHF on home oxygen, 4) hemodialysis, or 5) advanced neurodegenerative disease/dementia. The primary outcome was the retrieval of any existing resuscitation status documents. Documentation was obtained from a standardized review of forms accompanying the patient ("arrival documents") and electronic medical record ("EMR"). We measured the time to retrieve this documentation, and interviewed consenting patients to corroborate documentation with their current wishes.Results: Of 85 enrolled patients, only 33 (39%) had any documentation of resuscitation status: 28 (33%) had goals of care retrieved from the hospital EMR, and 11 (15%) from arrival documents (some had both). Patients from long-term care facilities were more likely to have documentation available (odds ratio 13 [95% CI 2.5-65] vs community-living). Of 32 patients who were able to be interviewed, 20 (63%) expressed "do not resuscitate" wishes. Ten of these 20 lacked any documents to support their expressed resuscitation wishes. Previously expressed resuscitation wishes took more than 5 minutes to be retrieved in 3 cases when not filed "one click deep" in our EMR.Conclusion: The majority of patients with AD, including half of those who would not wish resuscitation from cardiorespiratory arrest, did not have goals of care documents readily available upon arrival to the ED. Patients living in the community with AD appear to be at high risk for unwanted resuscitative treatments should they present to hospital in extremis . Having documentation of their goals of care that is easily retrievable from the EMR shows promise, though issues of retrieval, accuracy, and validity remain important considerations.